2020
DOI: 10.3390/v12030299
|View full text |Cite
|
Sign up to set email alerts
|

Co-Acquired Nanovirus and Geminivirus Exhibit a Contrasted Localization within Their Common Aphid Vector

Abstract: Single-stranded DNA (ssDNA) plant viruses belong to the families Geminiviridae and Nanoviridae. They are transmitted by Hemipteran insects in a circulative, mostly non-propagative, manner. While geminiviruses are transmitted by leafhoppers, treehoppers, whiteflies and aphids, nanoviruses are transmitted exclusively by aphids. Circulative transmission involves complex virus–vector interactions in which epithelial cells have to be crossed and defense mechanisms counteracted. Vector taxa are considered a relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…This study, together with previous results [10, 40], shows that barriers to gut exit or post-gut barriers were responsible not only for the non-transmission of ALCV by a non-vector population of A. craccivora but also for the low transmission of the vector population tested here. Interestingly, such barriers were detected in other virus–insect combinations in association with transmission defects.…”
Section: Conclusion and Prospectssupporting
confidence: 84%
See 2 more Smart Citations
“…This study, together with previous results [10, 40], shows that barriers to gut exit or post-gut barriers were responsible not only for the non-transmission of ALCV by a non-vector population of A. craccivora but also for the low transmission of the vector population tested here. Interestingly, such barriers were detected in other virus–insect combinations in association with transmission defects.…”
Section: Conclusion and Prospectssupporting
confidence: 84%
“…This decrease may be due to hindrance to virus flow from the gut to these compartments and/or degradation of viral DNA in these post-gut compartments due to insect-defence mechanisms such as autophagy, already described in the whitefly B. tabaci for TYLCV [76, 77]. Based on a recent report, the excretion from the salivary glands is not expected to account for much of the virus decrease in the post-gut compartments [40]. Indeed, using the same Robinia population of A. craccivora as here and a nanovirus clone of faba bean necrotic stunt virus (FBNSV), this study showed that although the accumulation of the two viruses were similar in the head compartment, the excretion of ALCV was far lower than that of FBNSV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-infections of plant viruses can be propagated by vectors that acquired virions from co-infected plants, sequentially from singly infected plants, or by multiple vector individuals that acquired different viruses. Vector acquisition of two viruses does not ensure both will be transmitted, and the presence of two viruses can alter transmission rates of one or both viruses 4,10,11,2232,3441,4851 . Once acquired, two viruses may compete for binding sites required for retention in and transmission from their vectors 6,29,33,37,49,52 .…”
Section: Introductionmentioning
confidence: 99%
“…Once acquired, two viruses may compete for binding sites required for retention in and transmission from their vectors 6,29,33,37,49,52 . Order of acquisition sometimes has an antagonistic effect on virus transmission 4,10,34,36,38 and does not always benefit the virus acquired first 22,30,36 . Vector-plant interactions that occur during probing and feeding events can also induce host plant defenses that mediate infection dynamics.…”
Section: Introductionmentioning
confidence: 99%